Leakage and trapping characteristics in Au‐free AlGaN/GaN Schottky barrier diodes fabricated on C‐doped buffer layers. Issue 5 (2nd May 2016) - Hu, Jie; Stoffels, Steve; Lenci, Silvia; You, Shuzhen; Bakeroot, Benoit; Ronchi, Nicolò; Venegas, Rafael; Groeseneken, Guido; Decoutere, Stefaan
Abstract: We investigate the DC and dynamic characteristics of AlGaN/GaN Schottky barrier diodes (SBDs) and the diodes with a gated edge termination (GET‐SBD) fabricated on unintentional doped (UID) and carbon‐doped AlGaN buffers. The off‐state characteristics of diodes fabricated on UID buffer are dominated by buffer leakage and buffer breakdown voltage (BV) at higher reverse voltage ( V R larger than 300 V). An improvement in diode leakage and BV can be obtained by fabricating the GET‐SBDs on C‐doped buffers. A pronounced R ON degradation of the AlGaN/GaN SBDs and GET‐SBDs on carbon‐doped buffers was observed by dynamic pulsed I − V characterization. This dynamic R ON degradation causes a clear forward current reduction for the AlGaN/GaN GET‐SBDs. From combined off‐state stress and current transient measurements on AlGaN/GaN SBDs, the collapsed current is recoverable and the R ON degradation is due to a temporary trapping mechanism occurring in the buffer. A distinct trap level of 0.57 eV from trap spectra has been extracted for the diode fabricated on C‐doped buffer, and the value was implemented in a TCAD simulator. The simulated results confirm a bulk trapping in the buffer layer for the SBD and show an additional trapping region in the GET‐SBD architecture.